2016
DOI: 10.1021/acs.jpcc.6b03840
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Products from Photoelectrochemical Reduction of 13CO2 by GaN-Si Based Tandem Photoelectrode

Abstract: Gallium nitride (GaN) has been shown to be a good photocatalyst for not only water splitting but also carbon dioxide (CO 2 ) reduction. To verify the catalytic reaction involved in CO 2 reduction, it is essential to confirm that the reaction products only come from dissolved CO 2 . Here, we report the results of 13 CO 2 -labeling experiments on a GaN-Si based photoelectrochemical system for each reduction product. It was found that the 13 C-based CO 2 was almost completely converted to formic acid (HCOOH), met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Moreover, the presented concept also clearly distinguishes itself from proof-of-concept approaches, demonstrating small-scale subassemblies for solardriven CO 2 reduction. 14,49,[55][56][57][58][59] The coupling of pure academic with engineered systems is urgently needed to mature CO 2 recycling processes and open the pathway towards a commercial application. This aspect is successfully addressed by the proposed concept.…”
Section: B Photoanode Composed Of Si Heterojunction Solar Cell and Nmentioning
confidence: 99%
“…Moreover, the presented concept also clearly distinguishes itself from proof-of-concept approaches, demonstrating small-scale subassemblies for solardriven CO 2 reduction. 14,49,[55][56][57][58][59] The coupling of pure academic with engineered systems is urgently needed to mature CO 2 recycling processes and open the pathway towards a commercial application. This aspect is successfully addressed by the proposed concept.…”
Section: B Photoanode Composed Of Si Heterojunction Solar Cell and Nmentioning
confidence: 99%
“…NiO cocatalyst improved not only the Energy Conversion Efficiency (ECE) of nitride photoelectrodes, but also their lifetime, which has been demonstrated to be at least 500 h 12 . It has also been confirmed that NiO/nitride photoelectrodes can be used to generate more complex byproducts than H 2 , such as formic acid and methane from CO 2 in artificial photosynthesis reactions 13 16 .…”
Section: Introductionmentioning
confidence: 92%
“…Connecting solar cells in series increases the voltage [92] i PA|C 3-Junction a-Si|CoO x Au 1.5 CO/95% n.r. 2.0% Sugano et al (2015) [94] i PA|C 4-Series Si heterojunction |Nifoam Cu-foam/Zn 5 CO/16% (syngas) 4.0% a) 0.77% a) Urbain et al (2017) [95] PA| [98] PV|A|PC Perovskite CoC i |Ni foam ZnO|ZnTe|CdTe|Au ≈0.8 CO/≈70% 0.43% 0.35% Jang et al (2016) [99] PV|PA|C Si N-doped TiO 2 Ni-N,S-graphene n.r. CO/n.r.…”
Section: Operational Considerationsmentioning
confidence: 99%